Initiation phase cellular reprogramming ameliorates DNA damage in the ERCC1 mouse model of premature aging - Paine, Patrick Treat; Rechsteiner, Cheyenne; Morandini, Francesco; Desdín-Micó, Gabriela; Mrabti, Calida; Parras, Alberto; Haghani, Amin; Brooke, Robert; Horvath, Steve; Seluanov, Andrei; Gorbunova, Vera; Ocampo, Alejandro (Frontiers in Aging, 2024)
Unlike aged somatic cells, which exhibit a decline in molecular fidelity and eventually reach a state of replicative senescence, pluripotent stem cells can indefinitely replenish themselves while retaining full homeostatic capacity. The conferment of beneficial-pluripotency related traits via in vivo partial cellular reprogramming (IVPR) significantly extends lifespan and restores aging phenotypes in mouse models. Although the phases of cellular reprogramming are well characterized, details of the rejuvenation processes are poorly defined. To understand whether cellular reprogramming can ameliorate DNA damage, we created a reprogrammable accelerated aging mouse model with an ERCC1 mutation. Importantly, using enhanced partial reprogramming by combining small molecules with the Yamanaka factors, we observed potent reversion of DNA damage, significant upregulation of multiple DNA damage repair processes, and restoration of the epigenetic clock. In addition, we present evidence that pharmacological inhibition of ALK5 and ALK2 receptors in the TGFb pathway are able to phenocopy some benefits including epigenetic clock restoration suggesting a role in the mechanism of rejuvenation by partial reprogramming.